2021
DOI: 10.1055/s-0041-1739034
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Intussusception in Children: A Retrospective Review of 212 Cases

Abstract: Objectives The primary objective of this study was to analyze and review the demographics of children operated upon for intussusception. Secondary objectives were to review the clinical characteristics, surgical procedures performed, postoperative complications, and outcome. Materials and Methods It is a single-institution, retrospective study and consists of children below the age of 12 years. This study was conducted at the author’s department of pediatric surgery for the past 21 years, from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…In addition, mortality rates related to surgical treatment for childhood intussusception are also reported to be less than 1% in developed countries. 11,16 Contrary to previous data, in developing countries, mortality associated with the management of intussusception in infants and children is much Most invaginations can be treated by nonoperative reduction via barium enema with fluoroscopy guidance and pneumatic reduction, and emergency surgery should still be performed in cases where nonoperative reduction fails. 17 In terms of surgical planning and patient management, it is critical to detect potential complications early, as delays can result in impaired intestinal circulation, which can lead to life-threatening secondary intestinal necrosis, perforation, or peritonitis, resulting in bowel resection and death.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, mortality rates related to surgical treatment for childhood intussusception are also reported to be less than 1% in developed countries. 11,16 Contrary to previous data, in developing countries, mortality associated with the management of intussusception in infants and children is much Most invaginations can be treated by nonoperative reduction via barium enema with fluoroscopy guidance and pneumatic reduction, and emergency surgery should still be performed in cases where nonoperative reduction fails. 17 In terms of surgical planning and patient management, it is critical to detect potential complications early, as delays can result in impaired intestinal circulation, which can lead to life-threatening secondary intestinal necrosis, perforation, or peritonitis, resulting in bowel resection and death.…”
Section: Discussionmentioning
confidence: 88%
“…10 Based on Ghritlaharey's (2021) retrospective study on pediatric invagination surgery <12 years in India for the period 2000-2021, it was found that ileocolic/colo-colic is the most common type of anatomy and was documented in n = 183 (86.32%) children, followed by ileo-ileal, n = 27 (12.73%), jejunojejunal, n = 1 (0.47%), and postoperative type, n = 1 (0.47%). 11 For pediatric patients who present with suspected SBO, an early surgical evaluation should be performed. 12 Conservative treatment, including fasting, nasogastric suction, and fluid therapy, is the first choice in adult patients and has a success rate of 16%-63%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meckel's diverticulum (inverted) is the most common lead point in 20%–50% of intussusceptions associated with PLPs. [ 2 ] Lipomas of the gastrointestinal tract (GIT) are the second most common benign lesions seen in colon (65%–75%), small intestine (20%–25%), stomach, and esophagus with a peak incidence in sixth or seventh decade. [ 3 ] Most GIT lipomas are asymptomatic and <50% of adult patients who have intestinal lipomas become symptomatic (intussusception, obstruction, or hemorrhage).…”
Section: Discussionmentioning
confidence: 99%
“…Present study consisted of 212 children below the age of 12-years, who were operated upon for intussusception during the study period of 21 years, with a brief review of the literature. [6][7][8]…”
Section: Introductionmentioning
confidence: 99%